2012
DOI: 10.1152/jn.00039.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neural targets for relieving parkinsonian rigidity and bradykinesia with pallidal deep brain stimulation

Abstract: Clinical evidence has suggested that subtle changes in deep brain stimulation (DBS) settings can have differential effects on bradykinesia and rigidity in patients with Parkinson's disease. In this study, we first investigated the degree of improvement in bradykinesia and rigidity during targeted globus pallidus DBS in three 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated rhesus macaques. Behavioral outcomes of DBS were then coupled with detailed, subject-specific computational models of neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
(54 reference statements)
2
41
0
Order By: Relevance
“…Three adult rhesus monkey (Macaca mulatta; one male, monkey K, 11.0 kg, 12 yr old; and two females, monkey R, 4.9 kg, 9 yr old, and monkey F, 8 kg, 25 yr old) were used in this study. Monkey K received an intraputaminal infusion of 3-nitropropionic acid (Agnesi et al 2013), whereas monkeys R and F were rendered moderately parkinsonian with the dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, as described previously (Hashimoto et al 2003;Johnson et al 2012). The animals were housed with environmental enrichment, provided with water ad libitum, and given a range of food options including fresh fruit and vegetables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three adult rhesus monkey (Macaca mulatta; one male, monkey K, 11.0 kg, 12 yr old; and two females, monkey R, 4.9 kg, 9 yr old, and monkey F, 8 kg, 25 yr old) were used in this study. Monkey K received an intraputaminal infusion of 3-nitropropionic acid (Agnesi et al 2013), whereas monkeys R and F were rendered moderately parkinsonian with the dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, as described previously (Hashimoto et al 2003;Johnson et al 2012). The animals were housed with environmental enrichment, provided with water ad libitum, and given a range of food options including fresh fruit and vegetables.…”
Section: Methodsmentioning
confidence: 99%
“…In monkey K the contact used was the most ventral contact within VPLo (contact 1, Ϫ0.3 mA, 130 Hz, 90-s pulse width). In monkey R the two contacts below and above the lamina separating the external and internal segments of GP were used, as this location was found to be the most effective setting at reducing bradykinesia and rigidity (contact 0 or 1, Ϫ1 V or Ϫ1.5 V, 135 Hz, 90-s pulse width) (Johnson et al 2012). This stimulation location was likely to affect both excitatory GP (GPe) and inhibitory GOP (GPi) efferent pathways directly, especially because DBS targeted to the GPi volume likely stimulates GPe efferents projecting through GPi .…”
Section: Methodsmentioning
confidence: 99%
“…First, it has been shown that deep brain stimulation (DBS) may antidromically activate afferent axons and fibers of passage (53)(54)(55)(56)(57)(58)(59), thus reaching structures not immediately downstream. Second, studies (57, 58) observed in 6-hydroxydopamine (6-OHDA)-intoxicated rats that the antidromic effects increase with the stimulation frequency and peak around 110-130 Hz.…”
mentioning
confidence: 99%
“…Motor behavioral effects of different stimulation parameters were also assessed using a semi-quantitative scoring system adapted from prior nonhuman primate, porcine and rodent studies [30][31][32][33][34]. Prior to these experiments, the maximal tolerable stimulation amplitude was determined for each DBS lead contact for each animal by a consensus of the veterinary and scientist team.…”
Section: Motor Behavior Assessmentsmentioning
confidence: 99%